2014
DOI: 10.1634/theoncologist.2013-0423
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Mellitus Is Associated With Increased Mortality in Chinese Patients Receiving Curative Surgery for Colon Cancer

Abstract: Background. We investigated the association between diabetes mellitus (DM) and the prognosis of patients with early colon cancer who had undergone curative surgery. Methods. From three national databases of patients in Taiwan, we selected a cohort of colon cancer patients who had been newly diagnosed with stage I or stage II colon cancer between January 1, 2004 and December 31, 2008 and had undergone curative surgery. We collected information regarding DM (type 2 DM only), the use of antidiabetic medications, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
3
25
0
1
Order By: Relevance
“…The increased risk of colorectal cancer is probably due to hyperinsulinemia, hyperglycemia and chronic inflammation . Several studies have examined the overall survival in patients with diabetes and colorectal cancer, and most studies found a decreased overall survival . Studies regarding the cancer‐specific mortality have shown conflicting results; several studies reported that diabetes increases the cancer‐specific mortality, but some showed no effect .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased risk of colorectal cancer is probably due to hyperinsulinemia, hyperglycemia and chronic inflammation . Several studies have examined the overall survival in patients with diabetes and colorectal cancer, and most studies found a decreased overall survival . Studies regarding the cancer‐specific mortality have shown conflicting results; several studies reported that diabetes increases the cancer‐specific mortality, but some showed no effect .…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus and colorectal cancer share several risk factors including obesity and physical inactivity, and diabetes is proven to be an independent risk factor for developing colorectal cancer . Several studies have shown that patients with both colorectal cancer and diabetes have a lower survival compared to patients without diabetes, whereas other studies have reported no association . Metformin is the drug of choice for treatment of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…In our meta-analysis, year of publication ranged from 2003 to 2016, and the regions included 2 American countries[7, 1315, 18, 19, 27, 30, 33, 37, 41, 42, 45, 46], 6 European countries[6, 11, 17, 28, 32, 39, 40, 44], 2 Asian countries[8, 9, 12, 16, 20, 29, 3436, 38, 43, 47] and 1 Oceania country[31]; the included studies contained 15 retrospective[9, 10, 14, 16–20, 27, 33, 36, 37, 39, 41, 47] and 21 prospective[68, 1113, 15, 2832, 34, 35, 38, 40, 4246] cohort studies; the sample size ranged from 391 to 1056243, and the mean age of study ranged from 46.4 to 72.07. In DM ascertainment, 25 studies[6, 8, 9, 1115, 18, 19, …”
Section: Resultsmentioning
confidence: 99%
“…However, both the Kaplan-Meyer graphs of DFS and the multivariate analysis clearly showed a strong prognostic role of diabetes in our homogeneous cohort of patients independently from the etiology. A very recent study has shown that diabetes is associated with significantly short colon-cancer-specific survival in patients diagnosed with early tumor stage (I or II) and treated with curative surgery [24]. A recent meta-analysis of 26 observational studies was conducted to examine the association between pre-existing diabetes and CRC all-cause mortality, cancer-specific mortality and recurrence.…”
Section: Discussionmentioning
confidence: 99%